The effect of prolonged cold exposure on leukocyte indices of dairy cows - Mylostyvyi, Roman (Problems of Cryobiology and Cryomedicine, 2026)
The effect of prolonged winter cold exposure on leukocyte composition and integral leukocyte indices (ILIs) in Brown Swiss dairy cows was investigated. Cows in the cold stress group were exposed to low ambient temperatures for 10 days (mean –9.6 ± 2.1 °C, minimum –14 °C). Prolonged cold exposure was associated with a decrease in the total leukocyte count, an increase in the proportion of monocytes, and no signifi cant changes in other leukocyte subpopulations. Concurrently, decreases in the neutrophil-to-monocyte ratio (NMR), lymphocyte-to-monocyte ratio (LMR), and index of immune reactivity (IIR) indicated a shift in immune balance towards the monocytic component and reduced immune reactivity. Changes in leukocyte indices refl ected a restructuring of immune homeostasis and activation of nonspecifi c defence mechanisms under low-temperature exposure. The results demonstrate the applicability of leukocyte indices for assessing adaptive changes in dairy cows under prolonged cold exposure. Probl Cryobiol Cryomed. 2026; 36(2): 89—94